Photobiomodulation of 450 nm blue light on human keratinocytes, fibroblasts, and endothelial cells: an in vitro and transcriptomic study on cells involved in wound healing and angiogenesis - Shao, Jingbo; Clément, Sophie; Reißfelder, Christoph; Téoule, Patrick; Gretz, Norbert; Guo, Feng; Hajizada, Sabina; Uhlig, Stefanie; Mößinger, Katharina; Torre, Carolina de la; Sticht, Carsten; Yagublu, Vugar; et al. (Biomedicines, 2025)
Background: Blue light (BL) irradiation has been shown to induce photobiomodulation (PBM) in cells. Here, we investigate its influence on cell types involved in wound healing. Methods: Cellular responses of immortalized human keratinocytes (HaCaTs), normal human dermal fibroblasts (NHDFs), and human umbilical vein endothelial cells (HUVECs) after light treatment at 450 nm were analyzed by kinetic assays on cell viability, proliferation, ATP quantification, migration assay, and apoptosis assay. Gene expression was evaluated by transcriptome analysis. Results: A biphasic effect was observed on HaCaTs, NHDFs, and HUVECs. Low-fluence (4.5 J/cm2) irradiation stimulated cell viability, proliferation, and migration. mRNA sequencing indicated involvement of transforming growth factor beta (TGF-β), ErbB, and vascular endothelial growth factor (VEGF) pathways. High-fluence (18 J/cm2) irradiation inhibited these cellular activities by downregulating DNA replication, the cell cycle, and mismatch repair pathways. Conclusions: HaCaTs, NHDFs, and HUVECs exhibited a dose-dependent pattern after BL irradiation. These findings broaden the view of PBM following BL irradiation of these three cell types, thereby promoting their potential application in wound healing and angiogenesis. Our data on low-fluence BL at 450 nm indicates clinical potential for a novel modality in wound therapy.